TUC Congress Souvenir, 1902 - The Women's Trade Union League (1902)
1902 1880-1914 "TUC Congress Souvenir, 1902 - The Women's Trade Union League" [T0504.jpg], 1902, Trades Union Congress The Women's Trade Union League was founded as the Women's Protective and Provident League in 1874. It was dissolved in 1921 when its functions were merged with the TUC. Emily Strong, Lady Dilke, became leader of the League after the death of its founder, Emma Paterson, in 1886. Gertrude Tuckwell (1861-1951), her niece was secretary of the League 1896-1904 and editor of its journal 'Women's Trade Union Review'. From 1905, she was president of the League and, from 1908, of the National Federation of Women Workers. Mona Wilson was secretary of the League 1897-1903.